The unexpected discovery of the Afrotropical genus Tricorythus Eaton, 1868 (Ephemeroptera: Tricorythidae) from the Oriental region with description of a new species - Srinivasan, Pandiarajan; Sivaruban, T.; Barathy, S.; Isack, Rajasekaran (Zootaxa, 2022)
Tricorythus meenakshi sp. n., is described based on all the stages from Tamil Nadu, Southern India. This new Indian species is most closely related to the Afrotropical species T. discolor Burmeister and T. tener Kluge. The new species can be separated from others in the genus by: In male imago, i) body dorsally with a colorless median stripe from head to abdomen; ii) femur and base of the tibia of all legs dark, rest mostly colorless; and iii) penis shape; and in the larva, i) body slender with a light median stripe as in adult; ii) protoptera dark in both sexes; iii) mouthparts details; iv) tarsal claws denticulation; and v) shape of denticles on hind margins of abdominal terga. Previously, the genus Tricorythus Eaton was known only from the Afrotropical realm; this is the first record of this genus from the Oriental realm.